Belgium: Enhancing the Cost Efficiency and Flexibility of the Health Sector to Adjust to Population Ageing - Sorbe, Stéphane (OECD Publishing, 2013)
Belgium has a good record in delivering accessible care, but adaptation to population ageing will be complicated by the fragmentation of responsibilities in the healthcare system and a strong reliance on government regulations. The organisation of the system could be rationalised by giving sickness funds a more active role as promoters of cost-efficiency, better aligning the incentives of the different levels of government and focussing on medium-term budgeting. At the level of care providers, better information flows and incentive structures could facilitate addressing practice and efficiency variations and supplier-induced demand. This notably involves completing the shift to pathology-based budgets in hospitals, more capitation in the remuneration of doctors and measures to tackle the high spending on drugs. Once incentives for cost-efficiency are in place, a shift towards a more demand-driven system could be encouraged by phasing out over-prescriptive hospital regulations. In addition, relative remunerations of doctors should be revised regularly to ensure an adequate supply per specialty. In long-term care, home care, which is generally cost-efficient, could be further encouraged by giving more autonomy to patients to organise their care. This Working Paper relates to the 2013 OECD Economic Survey of Belgium (www.oecd.org/eco/surveys/belgium)
Keywords: Social Issues/Migration/Health; Economics; Belgium